HUMANITARIAN CRISIS AND DIGITAL ADVOCACY: UNPACKING THE ALL EYES ON RAFAH CAMPAIGN - Teguh Luhuringbudi; Purnama Putra; Fitri Liza; Mowafg Abrahem Masuwd; Dewi Nita Utami; Abdulnasir Dhaw Alsayd (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
The